2009
DOI: 10.5194/bg-6-15-2009
|View full text |Cite
|
Sign up to set email alerts
|

Vertical structure and diurnal variability of ammonia exchange potential within an intensively managed grass canopy

Abstract: Abstract. Stomatal ammonia compensation points (χ s ) of grass species on a mixed fertilized grassland were determined by measurements of apoplastic [NH ] slightly increased at the bottom of the canopy and these concentrations were very high in senescent plant litter. Calculated χ s values were below atmospheric χ a at all canopy levels measured, indicating that the grassland was characterized by NH 3 deposition before cutting. This was confirmed by the χ a profile, showing the lowest χ a close to the ground (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…5c). This indicates a large potential for NH 3 emission in agreement with that senescent leaves and litter are important NH 3 sources (Mattsson and Schjoerring, 2003;David et al, 2009;Herrmann et al, 2009). Harper et al (2000 suggested that NH 3 emission from foliage may persist over prolonged periods, most of the time occurring from the surface rather than via the stomata.…”
Section: Grass Seasonal Nh 3 Exchange Potentialsupporting
confidence: 76%
“…5c). This indicates a large potential for NH 3 emission in agreement with that senescent leaves and litter are important NH 3 sources (Mattsson and Schjoerring, 2003;David et al, 2009;Herrmann et al, 2009). Harper et al (2000 suggested that NH 3 emission from foliage may persist over prolonged periods, most of the time occurring from the surface rather than via the stomata.…”
Section: Grass Seasonal Nh 3 Exchange Potentialsupporting
confidence: 76%
“…Age-related differences in the NH 3 compensation point of Luzula sylvatica were also found to be considerable , with both apoplastic pH and NH + 4 concentrations increasing during leaf expansion and declining prior to senescence. Diurnal patterns of s are generally less systematic than seasonal ones, even if there can be a large degree of hour-tohour variability Herrmann et al, 2009;Flechard et al, 2010). Although diurnal cyles of NH 3 exchange fluxes have been observed in e.g.…”
Section: Temporal Variationsmentioning
confidence: 99%
“…This technique has been applied to several plant species in the field Herrmann et al, 2009;Mattsson et al, 2009a;Mattsson et al, 2009b). However, the extraction technique is subject to uncertainties regarding potential regulation of apoplastic pH and [NH but also inter-species gradients of χ s (Hill et al, 2001;Loubet et al, 2002;Schjoerring et al, 2002.…”
Section: Apoplastic Extraction Direct Determination Of Leaf Apoplastmentioning
confidence: 99%